2011
DOI: 10.1186/1756-3305-4-32
|View full text |Cite
|
Sign up to set email alerts
|

Are we paying too much attention to cardio-pulmonary nematodes and neglecting old-fashioned worms like Trichuris vulpis?

Abstract: Trichuris vulpis, the dog whipworm, causes an intestinal parasitosis of relevance in current canine veterinary practice. Its occurrence is well-known in pets, kennelled dogs and stray animals, and its eggs contaminate the ground in urban areas all over the world. Moreover, T. vulpis has been occasionally incriminated, though not convincingly substantiated, as a cause of zoonosis. This nematode is erroneously considered an "old-fashioned" pathogen with a consequent lack of up- to- date knowledge on several aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
108
0
9

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(120 citation statements)
references
References 51 publications
3
108
0
9
Order By: Relevance
“…Lower prevalences (0.2 %) were found in other Italian studies (Manfredi et al, 2003;Di Cerbo et al, 2008). The zoonotic potential of T. vulpis is considered notable (Traversa, 2011). Aonchotheca putorii was found in the intestine and also in the stomach (see Magi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower prevalences (0.2 %) were found in other Italian studies (Manfredi et al, 2003;Di Cerbo et al, 2008). The zoonotic potential of T. vulpis is considered notable (Traversa, 2011). Aonchotheca putorii was found in the intestine and also in the stomach (see Magi et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The zoonotic species include Echinococcus multilocularis, the etiological agent of alveolar echinoccocosis (AE) (Guerra et al, 2014), E. granulosus, less frequent in foxes, the etiological agent of cystic echinoccoccosis (CE) (Richards et al, 1995), ascarids and ancylostomids, which are responsible for visceral and cutaneous larva migrans syndromes (Richards et al, 1993;Vergles Rataj et al, 2013). The red fox is also the defi nitive host of many intestinal parasitic species responsible for minor zoonosis, such as Trichuris vulpis (Traversa, 2011), Mesocestoides litteratus, Mesocestoides lineatus (Fuentes et al, 2003), Dipylidium caninum (Chappell et al, 1990) and other species of the genus Taenia such as T. crassiceps (François et al, 1998). The fox is also the main reservoir for Trichinella spp.…”
Section: Introductionmentioning
confidence: 99%
“…Trichuris spp. was not common in the samples but the parasite has been reported from humans, pets, livestock and wild animals such as foxes and dogs (Traversa, 2011).…”
Section: Intensity Of Infection Of Gastrointestinal Parasites In Red mentioning
confidence: 99%
“…This, together with close similarity in egg morphology, which means that cases of cross-infections are undetected by standard methods, might be the reason why the zoonotic potential of T. suis has been ignored to date. In contrast, the larger eggs of the dog whipworm, T. vulpis are more easily identified and several cases of humans cross-infected by T. vulpis have been described, even though most of these cases have not been properly evaluated (reviewed by Traversa, 2011). Recently Areekul et al (2010) used molecular methods and found that 11% of the Trichurispositive children in Thailand had T. vulpis eggs in their faeces, suggesting that this parasite should be considered a zoonosis in this area.…”
Section: Biologymentioning
confidence: 99%